Utilization of Green Diluent on the Removal for Heavy Metal Contaminants Using Emulsion Liquid Membrane - Kharitas Insani; H Bahti, Husein; Pratomo, Uji; Fauzia, Retna; Santhy Wyantuti; Fajar Firmansyah (Al-Kimia, 2024)
Growing industries and human activities have increased the amount of waste containing heavy metals, potentially toxic to human health and the environment. Conventional methods for handling heavy metal wastes have limitations, so the current emerging technique is emulsion liquid membrane (ELM), which is easy and inexpensive and leads to green chemistry. The composition of ELMs generally consists of surfactant, extractant, stripping agent, and diluent. In this article, the focus is on the use of environmentally sustainable diluents derived from vegetable oils. The diluent acts as a solvent for the extractant, helping form a stable emulsion and lowering the emulsion breakage percentage. This article aims to evaluate the potential use of vegetable oils as diluents in the Emulsion Liquid Membrane (ELM) process to improve emulsion stability and heavy metal extraction efficiency.